The 346 Clause of TFEU Regulation in Different EU Member States - Kuzminskas, Vilius (Teisė, 2019)
The article discloses the fixed exclusion regulation of Clause 346 in the Treaty of Function of the European Union in different EU member states. A further assessment of different relevant judicial approaches to regulation are disclosed and evaluated in accordance with the European Court of Justice case law and procurement in the defense area doctrine.